Implementation of rover tank firefighting robot for closed areas based on arduino microcontroller - Ahmed Murad; Oguz Bayat; Hamzah M. Marhoon (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Recently, communication via the wireless systems become promising, since the wireless communication system provides several benefits such as the disposal of the wire usage, provides long-distances communication, and the disposal of periodic maintenance of data transmission lines. In robotic science, the wireless system unit is the main part of the mobile robot. Whereas, only wireless communication module responsible for transmitting commands from the transmitter (e.g. mobile or PC) to the receiver (i.e. robot brain) and vice versa. With the increase in population growth and the construction of the urban, fires have become widely spread. It is worth mentioning here that the lives of firefighters are in permanent danger where they may be exposed to the combustion or inhalation of toxic gasses associated with the combustion process. Therefore, become necessary to find effective ways to reduce these risks. In this paper, a rover tank robot is implemented for fire extinguishing in closed areas based on the Arduino microcontroller, flame sensor, and motion sensor. The robot has a small water pump installed on a servo motor to pump water, the first flame sensor placed on the right of the robot's front and the second to the left of the robot's front. When a fire is explored through a flame sensor, the water pump sprays water to the location of the fire. The robot is driven wirelessly utilising the Bluetooth HC-06 module and the Wi-Fi camera utilised for driving purposes. Besides, a passive infrared (PIR) sensor is used to detect the presence of any living organism inside the fire site to alert the robot driver that an organism requires a rescue.